First trimester examination of fetal anatomy: clinical practice guideline by the World Association of Perinatal Medicine (WAPM) and the Perinatal Medicine Foundation (PMF) - Nicola Volpe; Cihat Şen; Şifa Turan; Waldo Sepulveda; Asma Khalil; Daniel Rolnik; Valentina De Robertis; Paolo Volpe; Mar M. Gil; Petya Chaveeva; Themistoklis Dagklis; Ritsuko K. Pooh; et al. (Perinatal Medicine Foundation, 2022)
This recommendation document follows the mission of the World Association of Perinatal Medicine (WAPM) in collaboration with the Perinatal Medicine Foundation (PMF). We aim to bring together groups and individuals throughout the world for precise standardization to implement the ultrasound evaluation of the fetus in the first trimester of pregnancy and improve the early detection of anomalies and the clinical management of the pregnancy. The aim is to present a document that includes statements and recommendations on the standard evaluation of the fetal anatomy in the first trimester, based on quality evidence in the peer-reviewed literature as well as the experience of perinatal experts around the world.